Efficacy and Safety of Gemcitabine With Trastuzumab and Pertuzumab After Prior Pertuzumab-Based Therapy Among Patients With Human Epidermal Growth Factor Receptor 2–Positive Metastatic Breast Cancer: A Phase 2 Clinical Trial - Iyengar, Neil M. (JAMA Netw Open, 2019)
IMPORTANCE: Taxanes with trastuzumab and pertuzumab for initial treatment of human epidermal growth factor receptor 2 (ERBB2, formerly HER2)–positive metastatic breast cancer is associated with improved progression-free survival (PFS) and overall survival. While continued use of trastuzumab in therapeutic combinations after disease progression is standard, the efficacy of continuing pertuzumab is unknown. OBJECTIVE: To evaluate the efficacy and safety of pertuzumab in combination with gemcitabine and trastuzumab after prior treatment with pertuzumab for ERBB2-positive metastatic breast cancer. DESIGN, SETTING, AND PARTICIPANTS: This is a phase 2 single-arm clinical trial of dual anti-ERBB2 therapy after prior treatment with pertuzumab. The study took place at a single academic center from March 2015 to April 2017 among women with ERBB2-positive metastatic breast cancer, prior pertuzumab-based treatment, and 3 or fewer prior chemotherapy regimens. Data were analyzed between January 2019 and March 2019. INTERVENTION: Treatment consisted of gemcitabine, 1200 mg/m(2) (later amended to 1000 mg/m(2)) on days 1 and 8 every 3 weeks, plus trastuzumab (8-mg/kg loading dose, then 6 mg/kg) and pertuzumab (840-mg loading dose, then 420 mg) once every 3 weeks. MAIN OUTCOMES AND MEASURES: The primary end point was 3-month PFS. Based on prior trials, a target rate of 70% or higher was selected as the promising progression-free rate at 3 months. Secondary outcomes included safety, tolerability, and overall survival. RESULTS: A total of 45 patients (median [range] age, 57.1 [31.7-77.2] years) were enrolled; 22 (49%) were treated in the second-line setting, and 23 (51%) were treated in the third-line setting or beyond. Of these, 22 (49%) received prior trastuzumab emtansine (T-DM1). At a median (range) follow-up of 27.6 (8.3-36.0) months, 3-month PFS was 73.3% (95% CI, 61.5%-87.5%). Overall, median PFS was 5.5 months (95% CI, 5.4-8.2 months). Treatment was well tolerated, with no occurrences of febrile neutropenia or symptomatic left ventricular systolic dysfunction. CONCLUSIONS AND RELEVANCE: In this phase 2 trial, treatment with gemcitabine, trastuzumab, and pertuzumab after prior pertuzumab-based therapy for ERBB2-positive metastatic breast cancer was associated with a 3-month PFS rate of 73.3% and was well tolerated. Continuation of pertuzumab beyond progression was associated with apparent clinical benefit. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02252887